Quantifying jump-specific loads in beach volleyball by an inertial measurement device - Schmidt, M.; Meyer, E.; Jaitner, T. (International Journal of Sports Science & Coaching, 2021)
The ability to complete a large volume of high intensity jumps represents an important performance indicator in beach volleyball. Inertial measurement units are suitable tools to monitor those jump-specific loads but the applicability in beach volleyball lacks research. This study evaluates the accuracy of a commercially available inertial measurement device in beach volleyball for (i) jump count during match-play and (ii) jump height measurement under laboratory conditions. Jump count measures were compared to retrospective video analysis to determine precision and recall. Jump heights were referenced to three-dimensional motion analysis to determine typical errors of estimate, correlations and Bland-Altman statistics. Match-play analysis results in excellent precision (0.975) for a total of 439 jumps and recall values between 0.836-1.000 depending on jump type. Jump heights revealed good to excellent correlations for block (r = 0.81) and spike jumps (r = 0.90), with a mean bias of 2.61 and 7.69 cm, respectively. The device demonstrates good validity for measuring jump count as well as vertical displacement. Due to its potential for nearly real time feedback with constraints of limited resources, we assume that this device will have considerable benefits for quantifying jump-specific load in beach volleyball.